Vietnam War Stories: Innocence Lost, 1st edition - Herzog, Tobey C. (Routledge, 2020)
The Gulf War and its aftermath have testified once again to the significance placed on the meanings and images of Vietnam by US media and culture. Almost two decades after the end of hostilities, the Vietnam War remains a dominant moral, political and military touchstone in American cultural consciousness.